2005
DOI: 10.1179/crn.2005.016
|View full text |Cite
|
Sign up to set email alerts
|

A Change of Occlusal Conditions After Splint Therapy for Bruxers With and Without Pain in the Masticatory Muscles

Abstract: Bruxism has been suggested as an initiating or perpetuating factor in a certain subgroup of temporomandibular disorders (TMD), however, the exact association between bruxism and TMD remains unclear. This study aimed to demonstrate the difference in responses between bruxism and a subgroup of TMD to a full-arch maxillary stabilization splint from the standpoint of an occlusal condition. This study was conducted to verify the null hypothesis that there were no differences between bruxer groups with and without m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Fujii et al12 used articulating paper to examine the change in occlusal contacts preand post-splint treatment in bruxism patients with and without myofascial pain. However, the results may be debatable, given the unreliability of articulating paper noted above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fujii et al12 used articulating paper to examine the change in occlusal contacts preand post-splint treatment in bruxism patients with and without myofascial pain. However, the results may be debatable, given the unreliability of articulating paper noted above.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion criteria for the bruxism group were as follows12: 1) knowledge or awareness of bruxing (clenching and grinding of teeth during sleep or while awake); 2) masticatory muscle stiffness upon waking; 3) attestation by the subject's sleep partner to grinding noises; 4) presence of mucosal, buccal and/or lateral tongue ridging. Exclusion criteria for both the bruxism and control groups were as follows: 1) signs or symptoms of disk displacement, arthritis or arthrosis of the temporomandibular joint (TMJ); 2) diagnosis of a systemic disease that could affect the masticatory system (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Fujii et al 51 in a study of 30 patients with bruxism and no myofascial pain and 30 patients with bruxism and myofascial pain who were treated with maxillary ODs found that participants with myofascial pain showed a larger change in occlusal condition, measured by the number of tooth contacts, than patients with bruxism without myofascial pain. The study time was from 4 to 22 weeks, with a mean of 10.5 weeks.…”
Section: Occlusal Devices (Od)mentioning
confidence: 99%
“…Any oral splint has the potential for adverse events. There are reports 4‐6 of other splint types causing irreversible bite changes after use. In patients with and internal derangement of the temporomandibular joint, up to 6% developed an anterior disc dislocation without reduction during the first few weeks of treatment 4 .…”
mentioning
confidence: 99%
“…The percentage increased to 21% when only patients with previous intermittent jaw locking were included. In a study by Fujii and colleagues, bruxers with myofacial pain demonstrated occlusal changes at a greater frequency than those without myofacial pain while utilizing a maxillary stabilization appliance 5 . May and Garabadian utilized theoretical joint loading modeling to demonstrate that an oral appliance with anterior only contact reduces temporomandibular joint loading 6 .…”
mentioning
confidence: 99%